Particle swarm optimization of GaAs-AlGaAS nanowire photonic crystals as two-dimensional diffraction gratings for light trapping. (1st June 2022) - Zagaglia, Luca; Demontis, Valeria; Rossella, Francesco; Floris, Francesco
Abstract: Semiconductor nanowire ordered arrays represent a class of bi-dimensional photonic crystals that can be engineered to obtain functional metamaterials. Here is proposed a novel approach, based on a particle swarm optimization algorithm, for using such a photonic crystal concept to design a semiconductor nanowire-based two-dimensional diffraction grating able to guarantee an in-plane coupling for light trapping. The method takes into account the experimental constraints associated to the bottom-up growth of nanowire arrays, by processing as input dataset all relevant geometrical and morphological features of the array, and returns as output the optimised set of parameters according to the desired electromagnetic functionality of the metamaterial. A case of study based on an array of tapered GaAs-AlGaAs core–shell nanowire heterostructures is discussed.